A study on interpersonal meaning negotiated teacher-students classroom interaction in vocational high school - Tyas, Ghita Aning; Widhiyanto, Widhiyanto (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
Interaction and teaching learning process are two things that cannot be separated. Interaction is a main point or component in communication. Communication skill has to be mastered by students including Vocational students because they need this skill as preparation for their professional work in the future. A good communication is when it has meaning in interaction. Halliday & Matthiessen, (2014) stated that there are three potential meanings, one of them are interpersonal meaning. This study was aimed to analyse interpersonal meaning between teacher and students in the eleventh grade of SMKN 2 Purwokerto and how it construct their role through various kinds of interaction. There were two activities in gathering the data of this study: observation and interview. In analyzing the data, the researcher used Mood system proposed by Halliday & Matthiessen (2004). Theory from Harmer (2001) and Johnson and Paulston (1976, cited in Richard and Rogers 1986) also used to analyze the role relationship between teacher and students. The findings showed that teacher and students produced three types of speech functions (Mood clause) besides Non-typical Mood Clause and Minor clause. In the class, both teacher and students applied different types of classroom interaction in which they took many roles. It can be concluded that teacher and students delivered various types of clause, classroom interaction, and roles during the teaching learning process.